Get rid of the matrix C in this matrix equation: M(AB + CD) = X(EF + GH)

matricesmatrix equations

So this question is about multiplying both sides of a matrix equation by a matrix.

Let's say I have this equation: $M(AB + CD) = X(EF + GH)$

and I want to make D free from any multiplication, which method is correct?

$M(A C^{-1}B + D) = X(EC^{-1}F + GC^{-1}H) $

$M(C^{-1}AB + D) = X(C^{-1}EF + C^{-1}GH) $

$C^{-1}M(AB + CD) = C^{-1} X(EF + GH) $ (I premultiplied both sides with $C^{-1}$ but I don't know how that will remove the $C$ from the $D$)

Also, where can I find more resources about multiplying equations with the inverse of matrix to get rid of it? That is easy for normal algebra, but I think it is more complicated for matrices.

Assumptions:

-All matrices are invertible.

-All matrices are of the same size ($n $ by $ n$)

Thanks

Best Answer

Expand $$MAB + MCD = XEF+XGH$$ Subtract $MAB$ $$MCD = XEF+XGH-MAB$$ Multiply by $C^{-1}M^{-1}$ on the right $$D=C^{-1}M^{-1}(XEF+XGH-MAB)$$

Related Question